FEATURES OF CLINICAL MANIFESTATIONS AND RISK FACTORS OF ATOPIC CHILITISM IN CHILDREN - Muydinova B. A; Usmonov B. A (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The most significant occurrence of atopic cheilitis among the factors of the antenatal and postnatal development of the child turned out to be a history of exudative-catarrhal diathesis. The leading clinical signs of atopic cheilitis are lichenization of the skin of the corners of the mouth, swelling of the lips, small and large plate peeling, deep or multiple small cracks, itching of various intensities.